Public Communication of COVID-19 Prevention in Vulnerable and Marginal Groups Towards Strong and Prosperous Family Resilience in Sidoarjo - Sri Warjiyati; Nurul Asiya Nadifah; Marli Candra (Lembaga Penelitian dan Pengabdian Masyarakat, 2022)
The title of this research is